High-Pressure Oxygen Insufflation of the Sorbent in Complex Treatment of Clean Soft Tissue Wounds - Dmitry V. Arhipov; Alexandr A. Andreev; Аlexandr А. Glukhov; Dmitry A. Atiakshin; Anton P. Ostroushko; Sergey N. Boyev; Anastasiya Yu. Laptiyova (International Journal of Biomedicine, 2020)
Background: The aim of our research was to study the effectiveness of the potentiation of reparative processes in soft tissues using high-pressure oxygen insufflations of the sorbent (S-HPOI) in the experiment. Methods and Results: The study included 150 Wistar rats that were divided into 5 groups: four control groups and one experimental group. Each group included 30 animals. The identical soft tissue wounds were simulated in animals of all groups. No additional interventions were carried out in the animals of the control group (CG) 1; high-pressure oxygen and air insufflation of wounds were applied in animals of CG2 and CG3, respectively; sorbent applications were performed for wound treatment in animals of CG4. The technique of S-HPOI was applied in animals of the experimental group (EG). The results of the experiment were assessed immediately after the simulation procedure, and on Days 1, 3, 5, 7, and 14 after wound simulation. The use of the sorbent applications and S-HPOI contributed to a significant acceleration of reparative processes by 1.1-1.3 and 1.2-1.5 times, respectively, compared with the results obtained in animals of CG1. Conclusion: The use of high-pressure oxygen has practically no benefits in wound treatment compared to similar intervention using air jet.On the whole, S-HPOI resulted in the maximum reduction in the area of soft tissue wounds: by 74.0% in 3 days, by 99.5% in 10 days compared to the initial findings.